Homoseksualitas: Pelanggaran terhadap Fitrah Kemanusiaan: Studi Komparasi Kitab al-Qur’an dan Alkitab - Siti Maryam (Alif Lam: Journal of Islamic Studies and Humanities, 2022)
The issue of morality about homosexuals cannot be separated from the pros and cons. In Indonesia, this issue is still a hot topic of discussion among religious people. Some community members and religious leaders strongly reject homosexual behavior and others accept and provide support for homosexual perpetrators. Support for homosexuals comes from several Islamic religious leaders, according to him, the current rejection of homosexual behavior is essentially not purely Islamic. Likewise, with support from Christian religious figures, the leadership of the Vatican Catholic Church conveyed the statement that homosexual perpetrators are children of God who have rights in a family. The purpose of this paper is to complete the study of moral issues that develop in society, especially about homosexuality. There are three questions posed in this paper. First, how is homosexual behavior in the view of the holy scriptures of Muslims and Christians? Second, why does God punish people who behave homosexually? Third, how is the response to the perpetrators of homosexuality in today's life?. Of these three questions, the focus of the study in this paper is to present a historical picture of the Prophet Lut from the perspective of Islam and Christianity. After the data in question is obtained, then they are compared to see the similarities and differences. And in order to ground the text of the scriptures, the historical meaning of the people of the Prophet Lut in today's life is an important thing that needs to be known